Phenoloxidases of the white-rot fungus Marasmius quercophilus isolated from an evergreen oak litter (Quercus ilex L.) - Tagger, S; Périssol, C; Gil, G; Vogt, G; Le petit, J (Enzyme and Microbial Technology, 1998)
A white-rot basidiomycete, Marasmius quercophilus, was isolated from an evergreen oak litter. This fungus, which very thoroughly bleaches the whole leaf area, produces laccases, a property which has not been studied before. Except on a ground leaf medium, we did not reveal phenoloxidases other than laccases. M. quercophilus is able to transform many aromatic compounds which are by-products of lignin and tannin metabolism. We observed, for example, that lignin monomers, namely p-coumaryl, coniferyl, and sinapyl alcohols are oxidized at different rates by the extracellular crude enzyme extract. The highest production of laccases is obtained with shaking cultures on malt extract supplemented with Tween 80 (0.1%) and CuSO4 (0.5 mg l 21 ). These enzymes have an optimum activity at 80°C and a stable activity at 40°C for 18 h. The extracellular crude enzyme extract medium contains three isoenzymes with pI values of 3.8, 3.5, and 3.2. It is able to significantly reduce the kappa number (21.2%) of a kraft pulp without inclusion of any mediator
Keywords: aromatic compounds; kraft pulp; laccases; Lignin; Marasmius quercophilus; phenoloxidases; tannin monomers